Reducing regulatory risk to attract and retain FDI - Priyanka Kher; Trang Thu Tran; Sarah Hebous (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
Regulatory uncertainty has been a key concern for investors over the past few years, further exacerbated by the ongoing Covid-19 pandemic. This Perspective discusses a newly developed measure of regulatory risk and policy options for countries to minimize such risk along 3 dimensions: transparency, investment protection, and effective recourse.
Keywords: 330